Organisational Commitment as a Mediating Variable in the Relationship between Work Environment and Leadership on Employee Performance in Correctional Institutions - Ervan Yansen; Nur Laely; Angga Rizka Lidiawan (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to analyze the influence of leadership and work environment on employee performance at a Correctional Institution, as well as the mediating role of organizational commitment. The research method used is a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis. The results show that leadership does not have a significant influence on employee performance (β = 0.193, T = 1.506, P = 0.133), but has a positive influence on organizational commitment (β = 0.633, T = 9.985, P = 0.000). Organizational commitment does not have a significant influence on employee performance (β = 0.022, T = 0.162, P = 0.872), while the work environment has a significant influence on employee performance (β = -0.349, T = 4.107, P = 0.000) but not on organizational commitment (β = 0.063, T = 0.718, P = 0.473). Furthermore, organizational commitment does not mediate the relationship between leadership and work environment on employee performance (β = 0.014, T = 0.158, P = 0.874; β = 0.001, T = 0.088, P = 0.930). The implication of these findings indicates that improving employee performance in the Correctional Institution is not sufficiently achieved by merely enhancing leadership aspects or organizational commitment. Instead, improvements in a more conducive work environment and more effective managerial strategies are necessary. Recommendations for the Correctional Institution include enhancing leadership competency, improving work facilities, and implementing employee welfare programs. This study is expected to serve as a reference for academics and practitioners in the development of human resource management within the correctional environment.